The Effectiveness of Transformational Leadership: An Analysis of Employee Empowerment and Creativity in MSMEs - Eko Boedhi Santoso; Fatkhur Rochman; Izzatul Ulya (Jurnal Penelitian, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are facing increasingly complex business competition, requiring employees to continuously innovate and generate creative ideas to maintain competitiveness amid limited resources. However, in practice, creativity does not always flourish optimally without the support of the right work environment. The role of leaders becomes crucial because the relatively simple organizational structure makes interactions between leaders and employees more intense. This study aims to analyze the influence of transformational leadership style on employee creativity, with employee empowerment serving as the mediating variable. This study employs an explanatory quantitative approach, with data collected via a survey. The results show that transformational leadership style does not have a significant direct effect on employee creativity. Conversely, employee empowerment has a positive and significant effect on employee creativity. Furthermore, transformational leadership style was found to have a positive effect on employee creativity through employee empowerment. These findings indicate that employee empowerment acts as a full mediator in the relationship between transformational leadership style and employee creativity. This study confirms that transformational leadership does not always have a direct impact on creativity but requires an empowerment mechanism that makes employees feel trusted, have autonomy, are involved in their work, and feel confident in expressing their ideas. Therefore, organizations need to translate transformational leadership into tangible empowerment practices so that employee creativity can develop sustainably.